Artistic Versions of World War II in Ukrainian Socialist Realist Literature (1941-1943) - Kharkhun, V. P. (My University, 2017)
У статті досліджено український соцреалістичний канон 1941-1943pp. Уній стверджується, що канон цього лерюду відзначався відносною лібералізацією, яка виявилася в трьох тенденціях: модифікації функцій літератури, розширенні списку канонічних тем та образів, реввії радянського життя та політики Комуністичної партії. Для пер 'юду лібералізації канону характерні три наративи про війну. Офіційна версія війни продукована в драматичних творах Олек- сандра Корнійчука, реабілітаційна версія створена Павлом Тичиною в поемі "Похорон друга", ревізійна версія - Олександром Довженком у кіноповісті "Україна в огні". Стаття націлена на дослідження подібностей, відмінностей та протиріч у мистецькій інтерпретації' воєнного досвіду. Такий підхід спрямований на аналв літератури 1941-1943 pp. як зразок радянської пропаганди та водночас "справжнього" мистецтва, що відображає реальну трагедію війни. Ключові слова:
The paper deals with Ukrainian socialist realist canon of 1941-1943. It states that relative liberalization was the main feature of the canon of that period which is revealed in three tendencies: modificatbn of literature functbns, extensbn of canonical themes and images as well as revisbn of Soviet life and Communist party's policy. The three narratives of the war are indicative for the period of canon liberalizatbn. The official version of the war was offered in Oleksandr Komiychuk's plays, the rehabilitatbn versbn was created in Pavio Tychyna's Funeral of a Friend poem, and the revisionist version is found in Oleksandr Dovzhenko's Ukraine in Flames cinematic novel. The article is aimed at the expbratbn of similaritbs, differences and contradictbns in artistic interpretatbns of the war experience. This approach directed toward the analyses of 19411943 Ukrainian literature which can be codified as Soviet propaganda and at the same time as a "true" artistic works depicting the real tragedy of war period.
Keywords: Ukrainian socialist realist canon; rehabilitatbn and revisbnist versbns of the war; Soviet propaganda